Novel dinuclear platinum(II) Complexes containing mixed nitrogen-sulfur donor ligands - Hochreuther, Stephanie; Puchta, Ralph; van Eldik, Rudi (Inorganic Chemistry, 2011)
A series of novel dinuclear platinum(II) complexes were synthesized containing a mixed nitrogen-sulfur donor bidentate chelate system in which the two platinum centers are connected by an aliphatic chain of variable length. The bidentate chelating ligands were selected to stabilize the complex toward decomposition. The pK a values and reactivity of the four synthesized complexes, namely, [Pt 2(S 1,S 4-bis(2- pyridylmethyl)-1,4-butanedithioether)(OH 2) 4] 4+(4NSpy), [Pt 2(S 1,S 6-bis(2- pyridylmethyl)-1,6-hexanedithioether)(OH 2) 4] 4+ (6NSpy), [Pt 1(S 1,S 8-bis(2-pyridylmethyl)-1,8- octanedithioether)(OH 2) 4] 4+ (8NSpy), and [Pt 2(S 1,S 10-bis(2-pyridylmethyl)-1,10- decanedithioether)-(OH 2) 4] 4+ (10NSpy), were investigated. This system is of special interest because only little is known about the substitution behavior of dinuclear platinum complexes that contain a bidentate chelate that forms part of the aliphatic bridging ligand. Moreover, the ligands as well as the dinuclear complexes were examined in terms of their cytotoxic activity, and the 10NSpy complex was found to be active. Spectrophotometric acid-base titrations were performed to determine the pK a values of all the coordinated water molecules. The substitution of coordinated water by thiourea was studied under pseudo-first-order conditions as a function of nucleophile concentration, temperature, and pressure, using stopped-flow techniques and UV-vis spectroscopy. The results for the dinuclear complexes were compared to those for the corresponding mononuclear reference complex [Pt(methylthiomethylpyridine)(OH 2) 2] 2+ (Pt(mtp)), by which the effect of the increasing aliphatic chain length of the bridged complexes could be investigated. The results indicate that there is a clear interaction between the two platinum centers, which becomes weaker as the chain length between the metal centers increases. Furthermore, differences and similarities of the N,S-system were compared to the corresponding dinuclear N,N-system studied previously in our group. In addition, quantum chemical calculations were performed to support the interpretation and discussion of the experimental data. © 2011 American Chemical Society.
CRIS-Team Scopus Importer:2026-01-22